2017
DOI: 10.3390/jfmk2030030
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Malnutrition during Pregnancy and Its Effects on Brain and Skeletal Muscle Postnatal Development

Abstract: "Foetal programming" refers to nutritional and hormonal variations during pregnancy. A maternal proper diet has a fundamental role in decreasing pregnancy complications and to prevent possible diseases in postnatal life. In our narrative review, we analyze and discuss the role of malnutrition during pregnancy and its effects on pre-and postnatal development of embryos. Our review proposes a comprehensive and careful analysis of the studies in this field regarding malnutrition and foetal programming. Evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…The correct de nition of nutritional programming was indicated by 29.3% of the breastfeeding women and only 24.1% of the pregnant women, which reveals the limited knowledge of these women about the importance of a woman's diet and lifestyle to the fetus. Research indicates that both pre-pregnancy and during pregnancy weight have an impact on the health of the baby [34][35][36][37]. Among those surveyed, 24.1% of the pregnant women and 27.6% of the breastfeeding women indicated that the maternal BMI index determines the health of a newborn child.…”
Section: Discussionmentioning
confidence: 99%
“…The correct de nition of nutritional programming was indicated by 29.3% of the breastfeeding women and only 24.1% of the pregnant women, which reveals the limited knowledge of these women about the importance of a woman's diet and lifestyle to the fetus. Research indicates that both pre-pregnancy and during pregnancy weight have an impact on the health of the baby [34][35][36][37]. Among those surveyed, 24.1% of the pregnant women and 27.6% of the breastfeeding women indicated that the maternal BMI index determines the health of a newborn child.…”
Section: Discussionmentioning
confidence: 99%
“…Budaya makan dengan pola setengah porsi sayur dan buah, seperempat porsi karbohidrat, dan seperempat porsi protein tampaknya masih harus disosialisasikan secara masif dan terus-menerus di masyarakat Indonesia. [33][34][35] Pemahaman mengenai suplementasi mikronutrien pada dosis intervensi atau dosis rumatan rasanya juga belum banyak dimengerti oleh masyarakat dan bahkan tenaga kesehatan. Penegakan diagnosis insufisiensi atau defisiensi nutrisi sering terkendala dengan mahalnya biaya pemeriksaan dan kemampuan laboratorium dalam memeriksa komponen nutrisi tersebut.…”
Section: Neuroproteksi Pada Pertumbuhan Janin Terhambat Dengan Multim...unclassified
“…Optimal maternal nutrition and complementary feeding are critical for the health and well-being of mothers and young children. Adequate nutrition during pregnancy is essential for the proper growth and development of the fetus and can help to reduce the risk of complications during pregnancy and childbirth [ 1 – 3 ]. Similarly, optimal complementary feeding during the first two years of life is essential for the proper physical and cognitive development of young children and can help prevent malnutrition and micronutrient deficiency [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate nutrition during pregnancy and early childhood can help to prevent stunted growth and promote more optimal growth and development, which can have positive impacts on children’s health and educational outcomes. It can also help to reduce the risk of maternal and child morbidity and mortality, which can have a significant impact on the overall health and well-being of families and communities [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%